Transcriptomic and Histological Analysis of the Response of Susceptible and Resistant Cucumber to Meloidogyne incognita Infection Revealing Complex Resistance via Multiple Signaling Pathways - Li, Xvzhen; Sun, Yinhui; Yang, Yuting; Yang, Xiaopei; Xue, Wanyu; Wu, Meiqian; Chen, Panpan; Weng, Yiqun; Chen, Shuxia (Frontiers in Plant Science, 2021)
The root-knot nematode (RKN), Meloidogyne incognita, is a devastating pathogen for cucumber (Cucumis sativus L.) specially in production under protected environments or continuous cropping. High level RKN resistance has been identified in African horned melon Cucumis metuliferus (CM). However, the resistance mechanism remains unclear. In this study, the comparative analysis on phenotypic and transcriptomic responses in the susceptible cucumber inbred line Q24 and the resistant CM, after M. incognita infection, was performed. The results showed that, in comparison with Q24, the CM was able to significantly reduce penetration numbers of second stage juveniles (J2), slow its development in the roots resulting in fewer galls and smaller giant cells suggesting the presence of host resistance in CM. Comparative transcriptomes analysis of Q24 and CM before and after M. incognita infection was conducted and differentially expressed genes (DEGs) associated with host resistance were identified in CM. Enrichment analyses revealed most enriched DEGs in Ca2+ signaling, salicylic acid (SA)/jamonate signaling (JA), as well as auxin (IAA) signaling pathways. In particular, in CM, DEGs in the Ca2+ signaling pathway such as those for the calmodulin and calcium-binding proteins were upregulated at the early stage of M. incognita infection; genes for SA/JA synthesis/signal transduction were markedly activated, whereas the IAA signaling pathway genes were inhibited upon infection suggesting the importance of SA/JA signaling pathways in mediating M. incognita resistance in CM. A model was established to explain the different molecular mechanisms on M. incognita susceptibility in cucumber and resistance to M. incognita infection in CM.